Inferring shifts in tree species distribution using asymmetric distribution curves: a case study in the Iberian mountains - Urli, Morgane; Delzon, Sylvain; Eyermann, Audrey; Couallier, Vincent; GARCÍA-VALDÉS, Raúl; Zavala, Miguel Angel; Porté, Annabel J (Journal of Vegetation Science, 2013)
Questions The objectives of this study were to examine altitudinal shifts in tree species distributions over one decade to quantify the potential for tree migration. Location Spain. Methods We analysed presence–absence data using two successive surveys of the Spanish Forest Inventory in five Fagaceae tree species (two temperate: Fagus sylvatica and Quercus petraea, one sub-Mediterranean: Q. faginea and two Mediterranean: Q. suber and Q. ilex) in two mountain ranges (the Pyrenees and the Iberian system). Half of the fitted altitudinal distributions were skewed and required use of an asymmetric model for unbiased estimates of optimum altitude and changes in the probability of presence along the altitudinal gradient. For each species and mountain range, shifts were considered to have occurred when the difference in optimum altitude was significant or when differences in probability of occurrence between the two surveys demonstrated the occurrence of colonization or extirpation events. Results Overall, depending on species and mountain range, shifts in optimum altitude ranged between −34 m and +181 m. The altitudinal distribution of the Mediterranean species at the core of their latitudinal distribution range presented no sign of change. For the temperate and sub-Mediterranean Fagaceae species, the patterns demonstrated the existence of distribution changes over a 10-yr period. The largest, although not statistically significant, upward shift in optimum altitude was observed for Q. petraea in the Iberian system. More interestingly, its distribution indicated colonization events at higher altitudes. For Q. faginea in the Pyrenees, the shift in optimum altitude was the second largest and statistically significant, and was associated with large extirpation events at the lower altitudes. No evidence of shifts was observed for F. sylvatica. Conclusion This work demonstrates that changes in altitudinal distribution could occur over a 10-yr time period for tree species located at the southern limit of their distribution, such as some temperate and sub-Mediterranean oaks, whereas no movement was detected for Mediterranean oaks in the core of their distribution area.
Keywords: Altitudinal distribution; Fagus; FOREST; model; Optimum; Quercus

Differences between tree species seedling and adult altitudinal distribution in mountain forests during the recent warm period (1986–2006) - Lenoir, Jonathan; Gégout, Jean-Claude; Pierrat, Jean-Claude; Bontemps, Jean-Daniel; Dhôte, Jean-François (Ecography, 2009)
Spatial fingerprints of climate change on tree species distribution are usually detected at latitudinal or altitudinal extremes (arctic or alpine tree line), where temperatures play a key role in tree species distribution. However, early detection of recent climate change effects on tree species distribution across the overall temperature gradient remains poorly explored. Within French mountain forests, we investigated altitudinal distribution differences between seedling (≤50 cm tall and >1 yr old) and adult (>8 m tall) life stages for 17 European tree taxa, encompassing the entire forest elevation range from lowlands to the subalpine vegetation belt (50–2250 m a.s.l.) and spanning the latitudinal gradient from northern temperate to southern Mediterranean forests. We simultaneously identified seedlings and adults within the same vegetation plots. These twin observations gave us the equivalent of exactly paired plots in space with seedlings reflecting a response to the studied warm period (1986–2006) and adults reflecting a response to a former and cooler period. For 13 out of 17 species, records of the mean altitude of presence at the seedling life stage are higher than that at the adult life stage. The low altitudinal distribution limit of occurrences at the seedling life stage is, on average, 29 m higher than that at the adult life stage which is significant. The high altitudinal distribution limit also shows a similar trend but which is not significant. Complementary analyses using modelling techniques and focusing on the optimum elevation (i.e. the central position inside distribution ranges) have confirmed differences between life stages altitudinal distribution. Seedlings optima are mostly higher than adults optimum, reaching, on average, a 69 m gap. This overall trend showing higher altitudinal distribution at the seedling life stage in comparison to the adult one suggests a main driver of change highly related to elevation, such as climate warming that occurs during the studied period. Other drivers of change that could play an important role across elevation or act at more specific scales are also discussed as potential contributors to explain our results.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Altitudinal distribution; climate change; seedlings (PG); Tree species distribution